Prospeção e uso de probióticos autóctone isolados do intestino de Colossoma Macropomum no desempenho zootécnico e na profilaxia da aeromonose na larvicultura de Tambaqui - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This study aimed to investigate the feasibility and effectiveness of supplementation with strains of lactic acid bacteria isolated from the intestinal microbiota of healthy tambaqui, on the pathophysiological and zootechnical responses in larvae of the same species of chal-lenged Aeromonas hydrophila. Ten tambaquis were purchased from local fishermen from the Amazon River in Santarém-Pa. The animals were euthanized by deepening the anesthetic plane and the gastrointestinal tract was removed for seeding in a Petri dish containing TSA and MRS media plus Aniline Blue dye. The culture was obtained from the direct sowing of stomach and intestinal contents and the mix (intestine + feces). A total of 11 5 bacterial strains were isolated and characterized to investigate their in vitro viability and probiotic potential. Initially, Catalase tests and Gram staining were performed, and 66 of the isolates were positive for lactic acid bacteria. Subsequently, the hemolytic activity of positive bacilli with negative catalase was evaluated, in which 5 did not present he-molysis, and these were selected for the other analyses (I3, I1 0, F4, M1 3, and M1 4). For the probiotic characterization of the bacteria, the viability and growth of lactic acid bacteria were verified at different pH values (2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, and 9.0) for 1 2 h, as well as bile resistance, antagonist activity, auto- and co-aggregation, biofilm formation, antibiogram, hydrophobicity, and lyophilization tests. For molecular identification of the worked species, PCR was performed using three primers: Lac 1 and 2 for Lactobacillus sp., Bac, and 1 6S for Bacillus sp., and their products were separated by gel electrophoresis. The in vitro analysis was initially carried out by the pathogenicity test in 30 juvenile tambaquis, divided into 6 groups, 0.5 mL of the isolates was inoculated into the coelomic cavity, where it was verified that there was no mortality and/or clinical behavioral alterations or tissues in all animals. In larviculture, better zootechnical performance was verified in strains I3 and M1 3 in relation to the control, without alteration of morphophysiological development. Sepsis induced in the larvae improved the survival and innate immunity of larvae supplemented with M1 3 and M1 4. The preliminary results obtained in the tests showed that the isolates belonging to the genus Lactobacillus present characteristics of potential probiotics for tambaqui larvae. Prospecting their technological and functional potential is extremely important for sustainable aquaculture production.
Keywords: Bactérias lácticas; Producão animal; Endêmico; Peixe nativo; Larva de peixe; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA